Analysis of the Vasorelaxant Action of Angiotensin II in the Isolated Rat Renal Artery - Leposava Grbović; Jelena Djokić; Miroslav Radenković; Srðan Pešic (Elsevier, 2008)
Taking into consideration that mechanisms involved in the vasodilatator actions of angiotensin II have not yet been completely elucidated, the present study was undertaken in order to examine the mechanisms underlying the angiotensin II-induced relaxation of rat renal artery (RRA). Angiotensin II produced concentration-dependent and endothelium-independent relaxation of isolated RRA. Angiotensin II-induced relaxation was partially reduced by inhibitors of nitric oxide synthase and guanylyl cyclase. The remaining dilatation was inhibited by a potassium channel blocker, charybdotoxin. Precontraction of RRA with high concentration of K+partially reduced angiotensin II-evoked relaxation, while indomethacin, glibenclamide, apamin and barium did not alter the angiotensin II concentration-response curve. Losartan had no effect on angiotensin II effect. Oppositely, HOE 140 and PD123319, separately or in combination, partially antagonized vasorelaxation induced by angiotensin II. Complete blockade of RRA response was obtained after simultaneous incubation of all three receptor antagonists HOE-140, PD123319, and losartan; L-NOARG plus HOE-140; or PD123319 plus charybdotoxin. These results indicate that angiotensin II produces endothelium-independent relaxation of RRA, which is most probably mediated by the interaction of the NO-cGMP pathway and K+channels. Moreover, we can assume that AT1, AT2, and B2receptors are involved in the vasorelaxant effect of angiotensin II. Keywords:: angiotensin II, rat renal artery, vasorelaxation, K+channel, AT receptor